2009
DOI: 10.1111/j.1753-4887.2001.tb06958.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diets Containing Fish Oil and Vitamin E on Rheumatoid Arthritis

Abstract: Animal, tissue culture, and human studies have evaluated the effects of fish oil supplementation in patients with rheumatoid arthritis (RA) over the last two decades. These studies have clearly shown potentially beneficial changes in cytokine and eicosanoid metabolism. The overall clinical improvement, however, has been only moderate. European clinical trials have shown significant pain reduction in patients with RA treated with vitamin E. A recent animal study in RA‐prone mice evaluated the effects of vitamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Successively, several studies have demonstrated that long chain x3 polyunsaturated fatty acids (x3 PUFA), such as eicosapentaenoic acid (C20:5 x3, EPA), docosapentaenoic acid (C22:5 x3, DPA) and docosahexaenoic acid (C22:6 x3, DHA) were the active agents of marine food and fish oil (Shahidi & Wanasundara, 1998). The existing data suggest that x3 PUFA exert a neuroprotective action (Bousquet et al, 2008) and play a protective role in inflammatory diseases such as rheumatoid arthritis, inflammatory bowel diseases (ulcerative colitis and Crohn's disease) systemic lupus erythematosus, septicaemia and septic shock and in carcinogenesis (Belluzzi et al, 2000;Ling & Griffiths, 2000;Tidow-Kebritchi & Mobarhan, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Successively, several studies have demonstrated that long chain x3 polyunsaturated fatty acids (x3 PUFA), such as eicosapentaenoic acid (C20:5 x3, EPA), docosapentaenoic acid (C22:5 x3, DPA) and docosahexaenoic acid (C22:6 x3, DHA) were the active agents of marine food and fish oil (Shahidi & Wanasundara, 1998). The existing data suggest that x3 PUFA exert a neuroprotective action (Bousquet et al, 2008) and play a protective role in inflammatory diseases such as rheumatoid arthritis, inflammatory bowel diseases (ulcerative colitis and Crohn's disease) systemic lupus erythematosus, septicaemia and septic shock and in carcinogenesis (Belluzzi et al, 2000;Ling & Griffiths, 2000;Tidow-Kebritchi & Mobarhan, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…EPA and DHA have many functions, including antiplatelet aggregation, thrombosis delay, tumor inhibition, antirheumatic and eyesight protection (Carrero et al 2007;Tisdale 2003;Chapkin et al 2002;Bradley et al 2001;Lu et al 1996;Tidow-Kebritchi and Mobarhan 2001). With the study of fish oil progressing gradually, people's demands increasing year by year.…”
Section: Introductionmentioning
confidence: 96%
“…[17][18][19][25][26][27][28][29] There has always been concern over the instability of the very long-chain fatty acids and their susceptibility to oxidation. 30 Santos-Zago et al have indicated that feeding CLAs adequately supplemented with vitamin E accelerates CLA antioxidant activities. 31 Therefore, this placebo-controlled study was conducted in patients with RA receiving standard anti-rheumatic treatment to investigate any complementary anti-inflammatory effects of CLA, as well as the synergistic effects of vitamin E.…”
Section: Introductionmentioning
confidence: 99%
“…This may be mediated by several of the following mechanisms: modulating cytokines such as interleukin (IL)‐1, IL‐4, IL‐6, IL‐8 and tumor necrosis factor (TNF)‐α, decreasing peroxisome‐proliferator activated receptor‐γ activation possibly linked either directly or indirectly through nuclear factor‐κB (NF‐κB) activation, decreasing eicosanoid production such as prostaglandin E2 (PGE2) by inhibiting cyclooxygenase‐2 (COX‐2), decreasing nitric oxide, and/or decreasing expression of adhesion molecules and proteinase genes 17–19,25–29 . There has always been concern over the instability of the very long‐chain fatty acids and their susceptibility to oxidation 30 . Santos‐Zago et al .…”
Section: Introductionmentioning
confidence: 99%